Adaptation of tax legislation to wartime conditions - Панфілов, Олег Євгенович; Панфілов, О. Є.; Панфилов, Олег Евгеньевич; Panfilov, Oleh Ye.; Latkovskyi, Pavlo; Latkovskyi, P. P; Huhlei, Vitalii; Латковський, Павло; Латковський, Павло Павлович (My University, 2023)
After the adoption of Ukraine as a candidate for EU membership, there is a logical need to study effective ways of unifying the current tax legislation of Ukraine following the legislation of the EU countries. The general scope of this work was to define and integrate these changes into the legislation of Ukraine based on the analysis of the experience of foreign countries. This descriptive and analytical study was conducted by analysing legislative frameworks and historical data. Dialectical, normative-dogmatic, logical-semantic and formal-logical methods were used. The article analyses the international experience of tax changes in countries where martial law was introduced for different periods. It is considered what changes the tax legislation of Ukraine has undergone for business under the influence of the military aggression of the Russian Federation. The fundamental changes in the tax system of Ukraine as a result of the implementation of the tax reform, which is already taking place today, are considered, namely changes to such taxes as VAT, personal income tax, a single tax, excise, as well as the procedure for taxation of the military tax administration. Current and future changes to the tax system of Ukraine within the framework of the tax reform introduced since the beginning of the war in Ukraine are analysed. The international experience of tax reforms in countries where martial law was introduced was studied. As a result, constructive changes in the tax sphere are proposed, which will positively affect the formation of the country's budget.
Keywords: martial law; state budget; tax legislation; tax revenues; воєнний стан; державний бюджет; податкове законодавство; податкові надходження; Research Subject Categories::LAW/JURISPRUDENCE